2021
DOI: 10.1186/s13619-020-00071-3
|View full text |Cite|
|
Sign up to set email alerts
|

RhoA/Rock activation represents a new mechanism for inactivating Wnt/β-catenin signaling in the aging-associated bone loss

Abstract: The Wnt/β-catenin signaling pathway appears to be particularly important for bone homeostasis, whereas nuclear accumulation of β-catenin requires the activation of Rac1, a member of the Rho small GTPase family. The aim of the present study was to investigate the role of RhoA/Rho kinase (Rock)-mediated Wnt/β-catenin signaling in the regulation of aging-associated bone loss. We find that Lrp5/6-dependent and Lrp5/6-independent RhoA/Rock activation by Wnt3a activates Jak1/2 to directly phosphorylate Gsk3β at Tyr2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…In the future, a treatment approach that modulates the TGF-β1 signaling pathway might be effective in patients with CED ( 5 ). In a recent study, the inhibition of RhoA/ROCK prevented aging-associated bone loss ( 44 ). Similarly, our findings raise the possibility of a treatment for diseases in which TGF-β1 is abnormally activated, including CED.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, a treatment approach that modulates the TGF-β1 signaling pathway might be effective in patients with CED ( 5 ). In a recent study, the inhibition of RhoA/ROCK prevented aging-associated bone loss ( 44 ). Similarly, our findings raise the possibility of a treatment for diseases in which TGF-β1 is abnormally activated, including CED.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that Wnt signaling can activate Rho kinase through both canonical and non-canonical pathways [ 47 , 48 ]. Rho/Rho-kinase integrate Wnt-induced signals spatially and temporally to promote transcriptional and morphological changes in cells regulating multiple cellular processes, including cell polarity, proliferation, differentiation, and apoptosis [ 49 ]. Our findings in the current study suggest that activation of Rho signaling pathways by Wnt ligands may be an essential downstream mechanism of prostate branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This alteration might also explain the well-known increasingly reduced bone marrow cellularity in the course of life. The underlying change of MSC differentiation is achieved via different mechanisms, including altered cytokine levels, resulting in decreased Wnt-related signaling and intensified RhoA-related signaling ( 38 ) as well as reduced Runx2 signaling, which is important for osteoblastic differentiation ( 39 ). “Senescence” that can be attributed to (cumulative effects of) pro-inflammatory cytokines, and changes of the sympathetic nerve system during life affect MSC ( 40 ).…”
Section: The Role Of Mesenchymal Stem Cells and Their Progenies In Amlmentioning
confidence: 99%